SUBCLINICAL VASCULAR DAMAGE IN YOUNG ADULTS WITH TYPE 1 DIABETES MELLITUS. (June 2022) - Marcon, Denise; Tagetti, Angela; Giontella, Alice; Bortolotti, Stefano; Bonafini, Sara; Piona, Claudia Anita; Carletti, Lorenza; Trombetta, Maddalena; Maffeis, Claudio; Fava, Cristiano
Abstract : Objective: Type 1 Diabetes (T1DM) is a chronic disease, whose prevalence is increasing, especially during childhood. Patients are affected by several complications, including macrovascular complications, that can be diagnosed early as subclinical vascular damage. The aim of our study was to assess possible associations between markers of subclinical arterial damage and traditional cardiovascular risk factors with a special focus on peripheral (pBP) and central blood pressure (cBP). Design and method: The study included 172 adolescents (100 male and 72 female) whose mean age was 24, 72 ± 8, 66 years, mean duration of the disease was 13, 45 ± 9, 58 years and mean BMI was 23, 32 ± 3, 22 kg/m2. 40 of the subjects (23, 5%) had a BMI > or = 25 kg/m2. Peripheral blood pressure was assessed using a mercury sphygmomanometer. Central blood pressure, PWV and PWA were evaluated with a tonometer (SphygmoCor Xcel). CIMT and carotid distensibility (DC) were measured by a high-resolution echo-doppler analysis, using a 5–13 MHz probe, and then further elaborated with a dedicated hardware (Cardiovascular Suite, Quipu, Pisa, Italia). Finally, several metabolic parameters were measured in plasma. Results: In our sample, 17 patients (10, 1%) could be classified as hypertensive by sphygmomanometer (systolic and diastolic pBP: pSBP and/or pDBP > or = 140/90mmHg) and 48 patients (27, 9%) as hypertensive (cSBP and/or cDBP > or = 130/80mmHg) by central BP estimate. 116 patients (68, 8%) had DC under the range of normality and 1 patient PWV (0, 6%) above 10 m/sec. Glycaemic control was relatively poor (glycated haemoglobin 7, 83 ± 0, 98%). In multivariable models, cSBP was associated with markers of subclinical arterial damage [cIMT (beta = 0, 288 ± 0, 001, p < 0, 001), AIx75 (beta = 0, 257 ± 0, 071, p = 0, 001), PWV (beta = 0, 374 ± 0, 007, p < 0, 001), DC (beta = -0, 149 ± 0, 055, p = 0, 029)]. Conclusions: Among subclinical vascular damage indices, carotid distensibility was the most altered in this sample of young adults with T1DM. But all the investigated markers showed a close association with BP values rather than with the other traditional cardiovascular risk factors. Further studies are warranted to better define the role of BP, especially cBP, in the stratification of cardiovascular risk in T1DM patients.